UNDANG-UNDANG HATE SPEECH SEBAGAI INSTRUMEN PERLINDUNGAN KEBEBASAN BEREKSPRESI PERSPEKTIF HUKUM HAM - Rohmatullah Rohmatullah; Syamsuri Syamsuri (Hakam: Jurnal Kajian Hukum Islam dan Hukum Ekonomi Islam)
The phenomenon of hate speech in the digital era poses a significant challenge in balancing freedom of expression as a fundamental human right (HR) with the protection of individual rights and social harmony. Freedom of expression, guaranteed by Articles 28E and 28J of the 1945 Constitution, often clashes with the threats posed by hate speech, which can lead to discrimination, social conflict, and human rights violations. In this context, regulations such as the Electronic Information and Transactions Law (ITE Law) and Law No. 40 of 2008 play a crucial role in mitigating the negative impacts of hate speech. This study employs a normative juridical method with a literature study approach to analyze hate speech regulations in Indonesia and their alignment with human rights principles. The findings reveal that despite existing regulations, inconsistent enforcement and potential misuse remain significant challenges. Thus, a human rights-based and proportional approach, coupled with public education, is necessary to foster a safe and inclusive digital space.